Physiological and biochemical responses of tomato plants to white mold affected by manganese phosphite - Chaves, Joicy Aparecida Alves (2020)
Considering the potential of white mold, caused by the fungus Sclerotinia sclerotiorum (Lib.) de Bary, to reduce tomato production, this study aimed to determinate the effect of manganese (Mn) phosphite on tomato resistance by assessing the photosynthetic performance (gas exchange and chlorophyll a fluorescence), the activities of defense enzymes and those related to the antioxidant metabolism as well as the concentrations of photosynthetic pigments, malondialdehyde (MDA), superoxide anion (O 2- ), and hydrogen peroxide (H 2 O 2 ) on plants challenge with S. sclerotiorum. The in vitro assays showed that S. sclerotiorum mycelial growth was inhibited by Mn phosphite in a dose-response manner. The spray of Mn phosphite reduced white mold severity on the leaves of tomato plants. Additionally, higher foliar Mn concentration was observed on plants sprayed with Mn phosphite. The negative effects of S. sclerotiorum infection in the photosynthetic process were mitigated by Mn phosphite application as noticed by the values of net carbon assimilation rate, stomatal conductance to water vapor, transpiration rate, maximal photosystem II quantum yield, and concentration of photosynthetic pigments. The concentrations of MDA, H 2 O 2 , and O 2- on infected leaves were lower upon Mn phosphite spray. In general, the activities of defense enzymes and those related to the antioxidant metabolism were higher for the water-sprayed plants infected by S. sclerotiorum in comparison to those sprayed with Mn phosphite. Based on the results of this study, the application of Mn phosphite may represent a feasible alternative for white mold management in tomato plants. Keywords: Sclerotinia sclerotiorum. Alternative control. Photosynthesis. Host resistance